Perspectives on the Pseudomonas aeruginosa Type III Secretion System Effector ExoU and Its Subversion of the Host Innate Immune Response to Infection - Kierra S. Hardy; Maxx H. Tessmer; Dara W. Frank; Jonathon P. Audia (Toxins, 2021)
Pseudomonas aeruginosa is an opportunistic, Gram-negative pathogen and an important cause of hospital acquired infections, especially in immunocompromised patients. Highly virulent P. aeruginosa strains use a type III secretion system (T3SS) to inject exoenzyme effectors directly into the cytoplasm of a target host cell. P. aeruginosa strains that express the T3SS effector, ExoU, associate with adverse outcomes in critically ill patients with pneumonia, owing to the ability of ExoU to rapidly damage host cell membranes and subvert the innate immune response to infection. Herein, we review the structure, function, regulation, and virulence characteristics of the T3SS effector ExoU, a highly cytotoxic phospholipase A2 enzyme.